2007
DOI: 10.1097/mph.0b013e3181461662
|View full text |Cite
|
Sign up to set email alerts
|

Combined Neutrophil and Erythrocyte Agglutination in a 7-year-old Boy

Abstract: Leukoagglutination is a rare in vitro phenomenon, with demonstration of both temperature and/or ethylenediaminetetraacetic acid dependence. We report a case of combined leukocyte and erythrocyte agglutination in a 7-year-old male with Mycoplasma pneumoniae and Epstein-Barr virus coinfection. To our knowledge, this morphologic finding has not previously been described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Aggregation of lymphocytes (Lymphoagglutination) is an extremely rare, EDTA-dependent phenomenon and is far less frequent than Neutrophils agglutination [4,5]. Sometime, leucoagglutination is accompanied with platelet aggregation [6] or erythrocyte aggregation [7]. The phenomenon described here is distinct from artificial leucocyte aggregation (artifact) at the edge of a blood smear sometimes observed during blood smear preparation.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Aggregation of lymphocytes (Lymphoagglutination) is an extremely rare, EDTA-dependent phenomenon and is far less frequent than Neutrophils agglutination [4,5]. Sometime, leucoagglutination is accompanied with platelet aggregation [6] or erythrocyte aggregation [7]. The phenomenon described here is distinct from artificial leucocyte aggregation (artifact) at the edge of a blood smear sometimes observed during blood smear preparation.…”
Section: Discussionmentioning
confidence: 72%
“…Colon cancer [8], liver cell carcinoma [9] etc. ), infection or inflammation (chest infection or pneumonia [3,7,[10][11][12], gastroenteritis, mycoplasma, EV virus, Herpes simplex [3,7], etc. ), hepatic disorders, shock, or autoimmune disease [6].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some case studies reported patients coinfected with MP and EBV suffered more severe symptoms. [ 17 , 18 ] For example, Li et al presented a case of EBV and MP coinfection complicated with splenic infarction. [ 17 ] Combined leukocyte and erythrocyte agglutination was described in a 7-year-old patient with MP and EBV coinfection by Yenson et al [ 18 ] These together indicated that to some extent MPP children with EBV coinfection had a more severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…The aggregation of leukocytes may also be temperature-dependent 1 and sometimes is accompanied with red cell autoagglutination. 6 At times, leukoagglutination can be time-dependent when immediate processing abolishes the agglutination. In some patients,…”
mentioning
confidence: 99%